2023
DOI: 10.3390/healthcare11060796
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Associated Factors for Periodontal Disease among Type I and II Diabetes Mellitus Patients: A Cross-Sectional Study

Abstract: In Saudi Arabia, the prevalence of diabetes mellitus (DM) is high. DM is a risk factor for periodontal disease. The current study aimed to estimate the prevalence and potential associated factors for periodontitis among type I and II DM patients in Abha, Saudi Arabia. A cross-sectional study was conducted among patients with DM who attended the Periodontal Consultant Center at King Khalid University and Aseer Central Hospital, in Abha city, from January 2020 to January 2022. A questionnaire was used to collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Evidence has revealed that the prevalence of periodontitis among Saudi adults is significantly higher than among other populations [34]. Most of the periodontitis research in Saudi Arabia seems to focus on investigating periodontitis among high-risk groups of patients, such as those with obesity or diabetes; however, researchers have not frequently studied the prevalence rate of periodontitis [34,35]. The Al-Baha region is one of 13 regions of Saudi Arabia.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence has revealed that the prevalence of periodontitis among Saudi adults is significantly higher than among other populations [34]. Most of the periodontitis research in Saudi Arabia seems to focus on investigating periodontitis among high-risk groups of patients, such as those with obesity or diabetes; however, researchers have not frequently studied the prevalence rate of periodontitis [34,35]. The Al-Baha region is one of 13 regions of Saudi Arabia.…”
Section: Introductionmentioning
confidence: 99%